Frequent co-occurrence of high-grade dysplasia in large flat colonic polyps (>20 mm) and synchronous polyps - Zhan, Tianzuo; Hahn, Felix; Betge, Johannes; Kähler, Georg; Ebert, Matthias; Belle, Sebastian (BMC gastroenterology, 2015)
Background: Large colonic polyps are associated with advanced dysplasia, but prevalence and characteristics of synchronous polyps in patients with large flat colonic polyps are poorly investigated. This study aims to characterize clinicopathological features of large flat colonic polyps and their impact on occurrence and characteristics of synchronous polyps. Methods: A total of 802 patients that underwent endoscopic mucosal resection (EMR) of flat colonic polyps >20 mm from 2003 to 2014 in an academic endoscopy unit were retrospectively analyzed for size, location and histology of large polyps and synchronous polyps. Results: Average size of large polyps was 34.1 mm (range 20-150 mm, standard deviation 16.1 mm). Histology included 52.5 % adenomas with low-grade dysplasia (LGD), 26.7 % with high-grade dysplasia (HGD), 9.6 % serrated polyps and 11.2 % adenocarcinomas. The majority of large polyps were localized in the proximal colon (61 %). 72.2 % of adenocarcinomas were found in the distal colon, while 80.5 % of all serrated polyps were detected in the proximal colon. Increase in polyp size, advanced age and location in the distal colon were associated with presence of HGD/adenocarcinoma in large polyps, as identified by multivariate analysis. Synchronous polyps were detected in 67.2 % of patients undergoing complete colonoscopy during EMR. Presence of HGD/adenocarcinoma in the large polyp, localization of any synchronous polyp in the rectosigmoid colon and occurrence of multiple synchronous polyps were associated with presence of HGD/adenocarcinoma in synchronous polyps. Conclusions: Synchronous polyps are frequently found in patients with large flat colonic polyps. The prevalence of synchronous polyps with high grade dysplasia is highest in patients with large flat polyps containing HGD/adenocarcinoma.
Gesehen am 15.03.2018